(untitled) (Research, Society and Development, 2022)
The aim of this study was to verify the applicability of the Ohmic Model with variable ionic resistivity to the voltammetric zinc oxide growth on galvanized steel sheets, without chromate passivating film. Two kind of galvanized steel sheets were studied: one produced from a bath of molten zinc containing antimony and the other containing lead. The galvanized steel sheets produced from a bath containing Sb presented better performance against corrosion in comparison on with those produced from a bath containing Pb. The electrochemical experiments were performed in a buffer solution of pH 8.7 with of 0.3 mol L-1 H3BO3 plus 0.15 mol L-1 Na2B4O7. It was found that the passivating zinc oxide grown on the galvanized steel sheet containing Sb showed higher ionic resistivity than that of the galvanized sheet containing Pb. This can explain the corrosion results.